Motorcycle Red Box Evaluation at Signalized Intersections in Bogor: Traffic Flow, Occupancy Rate and Stop Line Violation - Agah Muhammad Mulyadi (Institut Teknologi Sepuluh Nopember, 2017)
The number of motorcycle’s population until the end of 2016 was reach the peak around 98.2 million units and the sales was reach 5.93 million units. The accumulation of motorcycle disorderly movement at signalized intersection during waiting at the red light is a negative impact due to high motorcycle population. The red box is an alternative solution to increase signalized intersection performance. The aim of this paper is to evaluate the implementation of Red Box for motorcycle in relation to traffic flow, occupancy rate and traffic violations. The traffic flow analysis used the Indonesian road capacity manual while analysis of the occupancy rate and traffic violation method used the guidelines of Red Box monitoring. Analysis of the result showed that after implementation of the Red Box, traffic flow increased up to 15.64%. The occupancy rate to the capacity increased around 22.70% to 38.40%. Meanwhile, the Red Box occupancy by motorcycle was only around 33.33% to 68.33%. The number of stop line violations decreased up to 89.88%